Monetary union, fiscal crisis and the preemption of democracy - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2011)
The European Monetary Union (EMU) has removed crucial instruments of macroeconomic management from the control of democratically accountable governments. Worse still, the EMU has systemically caused destabilizing macroeconomic imbalances that member states found difficult or impossible to counteract with their remaining policy instruments. And even though the international financial crisis had its origins beyond Europe, the EMU has greatly increased the vulnerability of some member states to its repercussions. Its effects have undermined the economic and fiscal viability of some EMU member states and have frustrated political demands and expectations to an extent that may yet transform the economic crisis into a crisis of democratic legitimacy. Moreover, present efforts by EMU governments to 'rescue the euro' will do little to correct the economic imbalances and vulnerabilities, but are likely to deepen economic problems and political alienation in both the rescued and the rescuing polities. – – Die Europäische Währungsunion hat ihren Mitgliedstaaten die wesentlichen Instrumente der makroökonomischen Politik entzogen. Zugleich ist die einheitliche europäische Geldpolitik die strukturelle Ursache makroökonomischer Ungleichgewichte, die die Mitgliedstaaten mit den verbliebenen Mitteln nicht ausgleichen können. Und obwohl die internationale Finanzkrise nicht von Europa ausging, hat die Währungsunion die Verwundbarkeit einiger Mitgliedstaaten für deren Auswirkungen beträchtlich gesteigert. Die Folgen für die Wirtschaft der betroffenen Länder sind verheerend, und je mehr deren Politik gezwungen wird, die Forderungen und Erwartungen ihrer Bürger zu enttäuschen, desto eher kann die ökonomische Krise auch die demokratische Legitimität zerstören. Überdies ignorieren die gegenwärtigen Maßnahmen zur 'Rettung des Euro' die strukturellen Ursachen der ökonomischen Ungleichgewichte, und sie werden deshalb eher zur Verschärfung der ökonomischen Probleme und der politischen Frustration in den Geber- wie in den Nehmerländern beitragen.
Keywords: 300; Europäische Wirtschafts- und Währungsunion; Finanzmarktkrise; Währungskrise; Wirtschaftskrise; Demokratie; Legitimität; EU-Staaten